THUNDERCLAP HEADACHE: ARE WE INVESTIGATING SUFFICIENTLY?. Issue 10 (9th September 2014) - Graham, Neil
Abstract : Introduction: Non-traumatic thunderclap headache (TCH, a sudden-onset severe headache) is a concerning presenting symptom as it may indicate serious pathologies including subarachnoid haemorrhage (SAH). Secondary causes must be comprehensively excluded before primary headache is diagnosed. Objectives: To assess the management of TCH against a standard of acute neuroimaging (CT/MRI) followed by lumbar puncture (LP) where this is negative, with referral for further investigation if initial tests are non-diagnostic. Methods: Retrospective audit of electronic records of patients aged >15 years presenting with headache over one year at a District General Hospital, with casenote review to identify true TCH. Results: 58 probable cases of TCH were identified from 444 attendances coded 'headache' over one year, with acute neuroimaging in 145 cases showing four SAHs, six infarcts, five tumours, a cyst and one hydrocephalus. LP was performed in 20% of cases with non-diagnostic imaging, identifying two SAHs, two bacterial and one viral meningitis. No evidence of onward referral or further imaging after non-diagnostic LP was found. Conclusions: Emergency department doctors appear to employ an appropriately low threshold for neuroimaging in TCH, however there is little evidence that LPs are sufficiently performed where imaging is negative, or that further investigation is arranged following negative LP.